Изучение относительного роста некоторых внутренних органов общественных полевок популяции целинной степи Аскания-Нова - Емельянов, И.Г. (Вестник зоологии, 1976)
Positive allometry of the liver and negative allometry of the adrenal glands, kidneys and heart are established for M. socialis P a l l. Differences in the relative growth rate are observed for individuals of various sex and age. Seasonal variability of the relative growth rate of viscera was determined in animals of the same age. The correlation strength changes with age which permits supposing the existence of endogenic regulation of characters' correlation.